2008
DOI: 10.1208/s12248-008-9011-1
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic and Metabolic Differences Between Dog Breeds: Their Impact on Canine Medicine and the Use of the Dog as a Preclinical Animal Model

Abstract: Abstract. There is limited information describing species related pharmacogenetic differences in animals. Despite the lack of genetic information in veterinary medicine, breed specific responses to endogenous and exogenous substances have been reported across many species. This finding underscores the importance of obtaining insight into the genotypic and phenotypic variation present across breeds. This article provides a summary of the literature pertaining to canine breed differences in physiology, drug resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 58 publications
1
50
0
7
Order By: Relevance
“…This lower percent body fat can result in higher serum drug concentrations as compared to that seen in breeds with a higher percent body fat (Zoran, Riedesel, & Dyer, ). Breed‐related differences could cause dissimilarities in gastrointestinal transit time, intestinal fermentation, and drug disposition (Fleischer, Sharkey, Mealey, Ostrander, & Martinez, ). It has been reported that the long transition time causes prolongation in both gastric emptying time and small intestine transit time between breeds (Weber et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This lower percent body fat can result in higher serum drug concentrations as compared to that seen in breeds with a higher percent body fat (Zoran, Riedesel, & Dyer, ). Breed‐related differences could cause dissimilarities in gastrointestinal transit time, intestinal fermentation, and drug disposition (Fleischer, Sharkey, Mealey, Ostrander, & Martinez, ). It has been reported that the long transition time causes prolongation in both gastric emptying time and small intestine transit time between breeds (Weber et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…These polymorphisms can lead to differences in drug exposure and could result in breed‐related differences in drug response. Also, the differences in drug response may affect the safety and/or effectiveness of the drug (Fleischer et al., ; Kamimura, ). The T max (5.33 hr) determined in the praziquantel group was longer than the sustained‐release praziquantel tablet (3.2 hr) (Hong et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Sur le plan génétique, pour déterminer les bases molé-culaires de ces affections, les mêmes approches que pour les maladies monogéniques peuvent être réalisées, grâce à davan-tage de cas ; de telles approches ont déjà permis de mettre en évidence des régions chromosomiques candidates pour des maladies auto-immunes comme le lupus érythémateux (Wilbe et al 2010) ou des cancers (Shearin et al 2012). Il est d'ailleurs à noter que pour certains cancers homologues entre les deux espèces, des essais cliniques, de phase 1 et 2 chez le chien, sont déjà en cours aux États-Unis afin d'identifier de nouvelles molécules ou de nouvelles séquences de traitement chez l'homme (Khanna et al 2006;Paoloni & Khanna, 2007 ;Fleischer et al 2008), qui pourront également être utilisées en médecine vétérinaire.…”
Section: Identification Des Bases Génétiques De Maladies D'intérêt Chunclassified
“…Table 1 summarizes the vast array of phenotypic domains relevant to human healthspan that can be assessed in dogs and that serve as the foundation for the development of a standardized, age-sensitive assessment of canine health. For some variables, such as T cell function, red blood cell mass, and kidney function, age-related decline is well characterized; in other instances, such as breed-specifi c differences in xenobiotic metabolism, the exciting groundwork is being laid (Fleischer et al 2008). Clearly, generating a complete array of age-specifi c data from the more than 350 canine breeds would be a laborious and time-consuming undertaking.…”
Section: Why Dogs Why Nowmentioning
confidence: 99%